The Right to Petition in the Italian Revolutionary Triennium (1796-1799) - Cecilia Carnino (Journal of Interdisciplinary History of Ideas)
The goal of this article is to contribute to the study of the historical trajectories of petitioning, focusing on the Italian Democratic Triennium (1796-1799). The aim is to examine how, within the framework of the new political-institutional regime of democratically-inspired republics, petitioning was conceptualised primarily as an instrument of political participation, interest representation, and the protection of rights vis-à-vis the constituted authorities. The focus will be on the right to petition from the perspective of ideas, intellectual history, and political cultural history. The first part of the article will deal with the right of petition in the Constitutions of the Italian Revolutionary Triennium by comparing the various Italian republican experiences and also taking into account the fundamental model represented by the French constitutions. The second part will focus on the debates on the right to petition that took shape in the context of the Cisalpine Republic, particularly in the sessions of the Grand Council (Gran Consiglio), the lower chamber of the legislative body. It was precisely the members of the Grand Council, who developed the most articulate reflections on the right to petition and on petitions as an instrument of political participation, of defining and defending public interests, and also of protecting citizens against the authorities.